Insular dysfunction and descending pain inhibition in anorexia nervosa. (2nd July 2012) - Bär, K.‐J.; Berger, S.; Schwier, C.; Wutzler, U.; Beissner, F.
<x xml:space="preserve">Abstract</x> Objective: Reduced perception of pain is a well‐established phenomenon in patients with anorexia nervosa (AN). We tested the hypothesis that altered processing of pain within the insula might account for reduced perception of pain. Method: Heat pain thresholds were obtained in nineteen patients with AN and matched controls. Thereafter, a thermode was used to deliver thermal painful stimuli to the right arm during functional magnetic resonance imaging (fMRI) measurements. Stimuli were initiated for 10 s from a baseline resting temperature (32°C) to three different levels (37, 42, 45°C). Results: Significantly increased heat pain thresholds were observed in patients. A stronger activation during heat pain perception was found in the left posterior insula in controls. In contrast, higher levels of activity were shown in the ipsilateral pons in patients when compared to controls. In patients, we found a significant interrelation between the depression score (Beck depression inventory) and heat pain activations. Conclusion: We suggest that reduced activity in the left posterior insula might contribute to increased pain thresholds in patients, while increased activations in the right anterior insula and pons mirror augmented sympathetic modulation putatively related to amplification of adrenergic descending pain inhibition. In addition, pain thresholds and brain activations were influenced by disease‐inherent depressed mood.